Peranan Dan Implementasi Digital Marketing Sebagai Media Pemasaran Corndog.An Untuk Meningkatkan Jangkauan Atau Impresi - Nanda, Putri Widiyanti; Suprayitno, Suprayitno; Yoppi, Syahrial (Society : Jurnal Pengabdian Masyarakat, 2023)
Digital marketing is one of the marketing strategies that utilize the internet and information technology to increase reach or impressions. Digital marketing can be said to be able to help suppliers establish relationships with customers to increase a sense of customer loyalty. Digital marketing is often used by several companies. In addition, digital marketing has Another factor that influences customer loyalty is customer satisfaction. Therefore maintaining old customers is maintaining customer loyalty or a sense of trust. An era that is growing rapidly than from that the "Corndog.an" business uses digital marketing as a marketing medium.